Pengaruh Tingkat Kebugaran Jasmani Terhadap Hasil Belajar Bolabasket Mahasiswa Program Studi Penjaskesrek Angkatan 2018 - Idris Moh Latar; Josiano J.T. Tomasoa (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to look at the effect of the level of physical fitness on the learning outcomes basket ball of the 2018 classmates of the Penjaskesrek study program with a sample of 50 people. The methodology used in this study is an evaluative survey by measuring students' physical fitness and basketball learning outcomes. The research results show; (1) high fitness students with a mean value of 81 learning outcomes 81, (2) students with moderate fitness mean mean 7.8 basketball learning outcomes 84, while (3) students with low fitness 6.7 basketball learning outcomes 83. Based on the results of this study concluded that physical fitness had no effect on student basketball learning outcomes. This can be influenced by other factors, namely motivation to learn both in theory and practice.